Simulation of bioconversion processes using larvae of the black soldier fly in the disposal of food waste in hospitals - O. E. Krotova; K. S. Savenkov; A. M. Anokhin; A. S. Chernyshkov; A. A. Eroshenko (Современная наука и инновации)
Food waste is a social problem because it reduces the amount of safe and nutritious foods, increases the risk of infection due to improper disposal, attracts pests, promotes the growth of harmful bacteria and exacerbates environmental problems that threaten agricultural productivity. Research objectives: to find out how hospital food waste can be converted into nutrient-rich animal feed and fertilizers by setting standards based on the amount of food waste coming from inpatient patients; to analyze how various waste treatment methods affect the growth and absorption of nutrients by larvae. This study is relevant because it examines the use of larvae of the black soldier fly Hermetia illucens (H.Illucens) as a bioconversion agent in hospital settings. This is a relatively unexplored approach that promises the production of high-quality biomass for animal feed and organic matter. An effective model will help optimize the bioconversion process, thereby increasing the efficiency and effectiveness of food waste processing. Thus, this study may improve our understanding of food waste management in hospitals, especially in previously unexplored areas.